Critical perspectives on urban redevelopment - Gotham, Kevin Fox. (Amsterdam ; New York : JAI, 2001)
This is the fifth volume in a series which studies research in urban sociology, this work is an analysis of race and ethnicity in urban areas.
Urban development, past and present / Kevin Fox Gotham -- Monuments of tomorrow: industrial ruins at the millennium / James Dickinson -- City redevelopment policies and the criminalization of homelessness: a narrative case study / Adalberto Aguirre, Jr. and Jonathan Brooks -- Innovation, speculation, and urban development: the new media market brokers of New York City / Michael Indergaard -- Regime structure and the politics of issue definition: urban development in Pittsburgh, past and present / Gregory J. Crowley -- On fragmentation, urban and social / t
Includes bibliographical references.
Description based on print version record.
Keywords: Urban renewal; Social research & statistics; Urban communities; Social Science -- Sociology -- Urban